The Implementation of Equidistance Line on Maritime Delimitation between Indonesia-Australia in Perth Treaty 1997 - Sukma, Elsha Renata; Kusumaningarum, Rinindia; de Sousa, Freidelino Paixao Ramos Alves (Jurnal Ius Constituendum, 2024)
This article proposes some suggestions to the government in renegotiating the Perth Treaty to provide a solution for a definitive maritime boundary between Indonesia and Australia. Renegotiation of the Perth Treaty in terms of maritime delimitation between the two countries needs to be done in relation to the limitation of sovereignty of both countries. This treaty has never been ratified by both countries after the signing in 1998. The fundamental reason of Australia is associated with the independence of Timor-Leste in 1999 so that the rebus sic stantibus principle then applies. This research employed legal method to provide recommendations to the government as a basis for renegotiating the Perth Treaty according to international law. It also used a statutory and case approach. There are underlying reasons for the urgency of renegotiating the Perth Treaty using the median line with an equidistance line approach. The median line in UNCLOS 1982 has proven to provide progressive results regarding the maritime delimitation of countries. However the decisions of the International Court of Justice, resulted in various side effects with the use of the median line as a single effort to resolve maritime delimitation disputes. Therefore, a new solution is proposed, namely the median line with an equidistance line approach as the most effective method to create justice for each party. The equidistance line in international law serves as a legal resolution method, emerging from customary practices. It is recognized as new customary law for resolving maritime delimitation disputes between countries. Harmonisation of the median line concept using the equidistance line approach in resolving maritime delimitation disputes between Indonesia and Australia is a new approach that can be used based on the successful harmonisation of these two concepts in resolving delimitation disputes globally.